2021
DOI: 10.1029/2020tc006445
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic Controls on Surface Erosion Rates in the Longmen Shan, Eastern Tibet

Abstract: The Earth's topography results from the competition between internal processes driven essentially by tectonic fluxes and external forcing primarily affected by climate (Molnar & England, 1990). Acting as a bridge linking these two forcings, surface processes provide a source of multiple feedback mechanisms (Champagnac et al., 2012). Analyzing the amplitude and distribution of surface erosion can provide important insights to understand tectonic processes and/or climatic variation. Moreover, surface erosion mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 109 publications
2
10
0
Order By: Relevance
“…In recent years, many important achievements have also been published in this study of erosion rates along-strike or cross-strike in major faults (Xu and Kamp, 2000;Tan et al, 2015;Gao et al, 2016;Tan et al, 2017;Tan et al, 2019;Luo et al, 2021;Wang et al, 2021), as well as the syntectonic sedimentation deposited in the LMS active fold-thrust belt (Yan et al, 2013;Li et al, 2014;Li et al, 2016;Li C. et al, 2018;Luo et al, 2021). According to previous research on the regional erosion system, at least 4-5 km of strata have been eroded in the southern and central LMS at an erosion rate of 0 mm/yr to 1.0 mm/yr from the range front to the hinterland of the LMS foldthrust belt since the late Miocene (Tan et al, 2017;Shen et al, 2019;Ye, 2021;Wang et al, 2021). In addition, the differential erosion characteristics and syntectonic sedimentary loading along-strike of the LMS fold-thrust belt were further confirmed.…”
Section: Geological Settingmentioning
confidence: 87%
See 2 more Smart Citations
“…In recent years, many important achievements have also been published in this study of erosion rates along-strike or cross-strike in major faults (Xu and Kamp, 2000;Tan et al, 2015;Gao et al, 2016;Tan et al, 2017;Tan et al, 2019;Luo et al, 2021;Wang et al, 2021), as well as the syntectonic sedimentation deposited in the LMS active fold-thrust belt (Yan et al, 2013;Li et al, 2014;Li et al, 2016;Li C. et al, 2018;Luo et al, 2021). According to previous research on the regional erosion system, at least 4-5 km of strata have been eroded in the southern and central LMS at an erosion rate of 0 mm/yr to 1.0 mm/yr from the range front to the hinterland of the LMS foldthrust belt since the late Miocene (Tan et al, 2017;Shen et al, 2019;Ye, 2021;Wang et al, 2021). In addition, the differential erosion characteristics and syntectonic sedimentary loading along-strike of the LMS fold-thrust belt were further confirmed.…”
Section: Geological Settingmentioning
confidence: 87%
“…The 2008 M W 7.9 Wenchuan earthquake occurred deep in the interior of the LMS fold-thrust belt, 200 km northwest of the toe of the fold-thrust belt in the Sichuan basin (Hubbard et al, 2010), accompanied by the formation of coseismic reverse-and oblique-slip surface faulting by two large thrust faults (Lin et al, 2009;Liu-Zeng et al, 2009;Xu et al, 2009;Li et al, 2010). The occurrence of this earthquake showed that the LMS fold-thrust belt is still active nowadays and is characterized by strong tectonic uplift, rapid erosion, and devastating seismic hazards (Hubbard and Shaw, 2009;Xu et al, 2009;Yin, 2010;Gao et al, 2016;Tan et al, 2017;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Longmen Shan range, situated on the eastern margin of the Tibetan Plateau, stands out as one of the most prominent and imposing topographic escarpments worldwide (Figure 1a). It features steep terrain, with the average elevation rising from approximately 600 m in the Sichuan Basin to about 4000 m within the Tibetan Plateau, all within a relatively short horizontal distance of about 70 km [21] (Figure 1b). This range is characterized by deeply dissected landscapes shaped by the tributaries of the Yangtze River.…”
Section: Introductionmentioning
confidence: 99%
“…This range is characterized by deeply dissected landscapes shaped by the tributaries of the Yangtze River. The correlation between high peak elevations and substantial relief along the Longmen Shan has led to several interpretations, including the possibility of lower crustal flow at depth [15], an isostatic response to the erosion of the plateau margin [22], or variations in rock uplift linked to active faults [21,23]. The Longmen Shan range is divided into southern, central, and northern segments based on topography and structural deformation [26][27][28] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%